Bird communities of highway verges: Influence of adjacent habitat and roadside management (Acta Oecologica, 1999)
We have investigated the effects of landscape traversed and roadside structure on the use of highway verges by birds. Three contrasted landscapes were chosen in terms of human land use and vegetation structure: an intensive farmland, a pine plantation, and a matoral. The roadside sections varied in vegetation structure, width and profile. We recorded birds present in roadsides and adjacent habitats by transect counts over all seasons. Roadside bird species appeared for a great part similar to those of adjacent habitats. However, diversity and abundance in verges did not depend on that of adjacent habitats. Woody roadsides were compararable to hedges, as trees (and shrubs) in verges enhanced species richness and abundance of birds in the farmland and woodland sites. Width and profile of verges had less influence. In all sites, typical species of the habitat traversed partly avoided roadsides. On the contrary, numerous species associated with ‘rare’ habitats in one site preferred roadsides, provided that verge vegetation contrasted with the dominant habitat. It is concluded that birds responses to highways can vary greatly with landscape traversed and verge vegetation. Highway verges could be favorable to birds, if they constitute a complementary habitat to the dominant habitat within a landscape